The Effect of Using Closure Skill on Acquiring Some Vocabulary of Teaching Methods Course for Fourth Year Students of the Institute of Sport Education – Zakho - Ismael, Ayad Tariq; Taha, Taha Ramadhan; Saleeh, Adris Husain (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This study aimed to assess the effect of closure skills on vocabulary acquisition in teaching methods courses for fourth-year sport education students at the Institute of Sport Education in Zakho. The research addressed the gap in literature regarding the impact of closure techniques on specialized vocabulary learning in sport education teacher preparation. An experimental design was employed with 44 students divided into two experimental groups (teacher-led and student-led closure) and one control group. The educational program consisted of 12 instructional units focusing on command, basic positions, and derived positions in sport exercises. Data were collected through achievement tests and analyzed using ANOVA and t-tests. Findings revealed that both teacher-led and student-led closure skills significantly enhanced vocabulary acquisition compared to traditional methods, with no statistically significant difference between the two experimental approaches. The study demonstrated the effectiveness of closure skills in bridging the gap between content knowledge and effective teaching in sport education. These results align with broader educational research on the importance of structured reflection in learning. The comparable efficacy of teacher-led and student-led closure activities suggests flexibility in implementation for educators. Future research should explore long-term retention, technology integration in closure activities, and application across diverse sport education contexts. This study contributes to the refinement of sport education teacher preparation programs and offers insights for enhancing pedagogical practices in the field of physical education.